2012
DOI: 10.1128/jb.01502-12
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Transport in Escherichia coli Mutant Strains with Defects in Sugar Transport Systems

Abstract: In Escherichia coli, several systems are known to transport glucose into the cytoplasm. The main glucose uptake system under batch conditions is the glucose phosphoenolpyruvate:carbohydrate phosphotransferase system (glucose PTS), but the mannose PTS and the galactose and maltose transporters also can translocate glucose. Mutant strains which lack the enzyme IIBC (EIIBC) protein of the glucose PTS have been investigated previously because their lower rate of acetate formation offers advantages in industrial ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 68 publications
7
88
0
Order By: Relevance
“…The qualitative effects on q s and μ of deleting specific PTS and non-PTS transporters in strain W3110 are in agreement with results reported with mutant derivatives of E. coli strains MG1655 and AF1000 having some of the same gene deletions performed in this study [30-32]. However, the magnitude of q s reduction as function of specific gene inactivation differs from our results.…”
Section: Resultssupporting
confidence: 91%
“…The qualitative effects on q s and μ of deleting specific PTS and non-PTS transporters in strain W3110 are in agreement with results reported with mutant derivatives of E. coli strains MG1655 and AF1000 having some of the same gene deletions performed in this study [30-32]. However, the magnitude of q s reduction as function of specific gene inactivation differs from our results.…”
Section: Resultssupporting
confidence: 91%
“…For non-transformed E. coli DgalT cultured under glucose or glucose plus galactose, the growth curves were indistinguishable, since glucose is the preferred carbon source and galactose represents no toxicity in the presence of this hexose. This absent toxicity of galactose likely results from carbon catabolite repression exerted by glucose, which represses the galactose uptake systems GalP and Mgl (G€ orke and St€ ulke 2008; Misko et al 1987;Shimizu 2013;Steinsiek and Bettenbrock 2012). In the presence of glycerol, transported into E. coli through facilitated diffusion (Chu et al 2002), the growth rate was approximately half of that observed in the presence of glucose, confirming that this polyol is not as efficient as glucose as a carbon source, as previously described (Chu et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…The strains used in this study are either wild type E. coli NCM3722 strain 51,52 or its derivatives: NQ1261 (Δ ptsG , deleted of the gene encoding the main glucose transporter PtsG), which grows slowly in glucose medium 53 , NQ1468 used for measuring LacZα induction kinetics, and the WE2015 series of strains used for measuring the translational elongation rate of various proteins using the hybrid LacZα approach described below. E. coli MG1655 strain used in the ribo-seq study of Li et al 3 was also obtained directly from G. W. Li.…”
Section: Methodsmentioning
confidence: 99%